Post-earthquake spatio-temporal landslide analysis of Huisun Experimental Forest Station - Ming-Der Yang Hui-Ping Tsai (Terrestrial, Atmospheric and Oceanic Sciences, 2019)

(untitled)
The present study utilized satellite imagery and the Normalized Difference Vegetation Index (NDVI) to investigate the post-earthquake spatio-temporal changes of landslide for Huisun Experimental Forest Station (HEFS). Total 26 SPOT satellite images taken between January 1999 (before the Chi-Chi earthquake) and July 2016 shows that the total landslide area was fluctuated after the earthquake and then became stable after 2008. Overall, the long-term landslide trends of HEFS is approaching a stable stage in terms of the slightly increasing mean NDVI value with decreasing NDVI variance from 1999 to 2016 based on the linear regression and Mean-Variance analyses. Two large landslide areas in Xinsheng Village and along Meitangan River were identified as statistically significant hot spots. More than 50% of landslides in HEFS were observed in areas with S-facing and SE-facing slopes with the majority of landslides occurred at 500 - 1500 m elevation. The slope characteristic of landslides changed to a concentration in 30 - 40 degree after the Chi-Chi earthquake and changed again to a concentration in 20 - 30 degree after 2008. Based on the results of the frequency of landslide occurrence, the total landslide area was the largest in the 0 - 9 times category. In the 10 - 16 and 17 - 26 times categories, high percentages of landslides were found in SE-facing and S-facing slopes. An inverse relationship was found between the landslide areas and the distance to river channel in the 0 - 9 and 10 - 16 times categories. The results of spatio-temporal landslide analysis can be references for management and conservation strategies in HEFS.